2021
DOI: 10.1164/rccm.202003-0520oc
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Mucosal Immunotherapy with MV130 Prevents Recurrent Wheezing in Children: A Randomized, Double-Blind, Placebo-controlled Clinical Trial

Abstract: Rationale: Recurrent wheezing in children represents a severe public health concern. Wheezing attacks (WA), mainly associated with viral infections, lack effective preventive therapies. Objectives: To evaluate the efficacy and safety of mucosal sublingual immunotherapy based on whole inactivated bacteria (MV130) in preventing WA in children. Methods: A Phase 3 randomized, double-blind, placebo-controlled, parallel-group trial including a cohort of 120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 50 publications
3
52
0
1
Order By: Relevance
“…A proof of principle for this model has been recently provided by Nieto et al in a randomized placebo-controlled clinical trial (n = 120) [55]. In this study, mucosal sublingual immunotherapy based on whole inactivated bacteria (MV130) reduced the number of wheezing attacks (WA) and other secondary outcomes [55]. While this study supports the notion of IIT, it is still unclear regarding what the best timing for intervention should be.…”
Section: Microbiome-driven Interventions and Early Respiratory Health: The Novel Notion Of Innate Immune Trainingmentioning
confidence: 52%
See 1 more Smart Citation
“…A proof of principle for this model has been recently provided by Nieto et al in a randomized placebo-controlled clinical trial (n = 120) [55]. In this study, mucosal sublingual immunotherapy based on whole inactivated bacteria (MV130) reduced the number of wheezing attacks (WA) and other secondary outcomes [55]. While this study supports the notion of IIT, it is still unclear regarding what the best timing for intervention should be.…”
Section: Microbiome-driven Interventions and Early Respiratory Health: The Novel Notion Of Innate Immune Trainingmentioning
confidence: 52%
“…In the same way that pathogenic bacteria during early life may increase the risk for respiratory disorders, exposure to protective bacteria may serve as a primary prevention. A proof of principle for this model has been recently provided by Nieto et al in a randomized placebo-controlled clinical trial (n = 120) [55]. In this study, mucosal sublingual immunotherapy based on whole inactivated bacteria (MV130) reduced the number of wheezing attacks (WA) and other secondary outcomes [55].…”
Section: Microbiome-driven Interventions and Early Respiratory Health: The Novel Notion Of Innate Immune Trainingmentioning
confidence: 79%
“…More comprehensive wholeanimal data is available from experimental models, which collectively point towards myeloid precursor populations in bone marrow as the primary targets for OM85-mediated IIT effects 7,15 , likely responding to multiple TLR ligands present in this agent 9 . This may account for the similarity in clinical response profiles in children evident in the recent trial results reported for OM85 13,14 and MV130 3 , both of which are derived from TLR ligand-rich mixed bacterial lysates.…”
mentioning
confidence: 62%
“…This class of therapeutics is dominated by the agent OM85, derived from 8 major bacterial respiratory pathogens, which has been in widespread clinical use for over 30yrs in Europe and South America, for protection of at-risk young children and adults against sLRI and associated symptoms (reviewed 7,12 ). In addition to multiple investigations in older children and adults 12 , recent studies employing OM85 have demonstrated reduction in sLRI frequency and severity in preschool and early school age children 13 similar to that achieved with MV130 3 , and importantly have also demonstrated comparable safety/efficacy in infants preselected on the basis of high risk for atopy/asthma 14 . OM85 is also in current use in a large NIHfunded multi-centre trial (https://clinicaltrials.gov/ct2/show/NCT02148796) targeting similar outcomes.…”
mentioning
confidence: 97%
“…show how mesenchymal stem cells are able to uptake, process and retain a reservoir of the TLR ligands derived from inactivated bacteria (MV130), which can subsequently be transferred to dendritic cells. MV130 is a mucosal polybacterial preparation that induces trained immunity and prevents viral wheezing attacks in young children ( 8 ) and used in a proof of concept study in patients with hematological malignancies, showing beneficial effects in terms of infections incidence ( 9 ). The effect of the combination of a similar polybacterial preparation (MV140) used to prevent urinary tract infections with Candida albicans (V132) has been studied by Martín-Cruz et al.…”
mentioning
confidence: 99%